Coolie Children: Trinidad, B.W.I. - (:unkn) unknown (Stephens, Trinidad, 2008)
Photo of a group of East Indian children and babies.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Postcards; Children--Trinidad and Tobago; East Indians--Trinidad and Tobago; Trinidad and Tobago